(untitled) (Medicine Anthropology Theory, 2020)
This article focuses on the spatial significance of health care access, analyzing how state health programs effected sociospatial transformations in poor urban neighborhoods in Caracas, Venezuela. Starting in 2003, the leftist state constructed a parallel public health system to shift biomedical care from hospital emergency rooms to small clinics in neighborhood settings, arguing that it would improve the quality and accessibility of medical care for the poor. The new national health program, Barrio Adentro (Inside the Neighborhood), explicitly reorganized public medicine according to the pragmatic and symbolic significance of place. This article, based on fifteen months of ethnographic research in central Caracas, focuses on the meanings of these new health spaces for patients. Patients viewed the placement of clinics – and doctors – in barrios and working-class neighborhoods not only as logistically necessary but also as a moral and political commitment on the part of doctors and on the part of the state that employed them. In a context of marked spatial segregation along class lines, the placement of doctors ‘inside the neighborhood’ was symbolically significant because it marked such communities as deserving of services and challenged longstanding divisions between marginalized and privileged social groups in Caracas.